Proximate Analysis of Bycatch Fish and Probiotics Treatments towards the Good Aquaculture Practices - Sudirman Adibrata; Rufti Puji Astuti; Novyandra Ilham Bahtera; Rahmad Lingga; Fahmida Manin; Maulana Firdaus (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Bycatch small pelagic fish during the fishing season can be oversupplied so that its price goes down.  The study aims to analyze the proximate of local fish powder from the by-catch and probiotics of Probio_FM in the fish feed in Bangka Belitung. The method was the data compared with the Indonesian National Standard, SNI 01-2715-1996/Rev: 92 about the raw material of animal feed as fish powder and fish feed with six different treatments. The study found that the bycatch or trash from small pelagic fish could be used as a fish powder or fish feed. The proximate analysis on fish powder and fish feed with probiotics Probio_FM included as the quality of SNI. Crude protein values from 25.75% until 66.96% that was above SNI standard I (1.5%), II (2.5%), and III (3.0%) could be followed up into an economical business. Fermented activity from Probio_FM could degrade the protein and other components proximate such as ash content, crude protein, crude fat, crude fiber, calcium, Phosphor, and NaCl. The amino acids from protein were getting simpler and easier being absorbed by fish in culture or livestock farms. Probio_FM was assumed to degrade the protein value and other components proximate due to the utilization of nitrogen and ammonia derived from the process fish protein hydrolyzation of probiotic bacteria. The production of local feed should be implemented to reach feed security and very important to be developed into a community business. Proximate analysis of bycatch could support sustainable good aquaculture practices in the future.